Improving the Performance of Women's MSMEs in Palopo City through Work-Life Balance, Social Capital, and Knowledge Management - Marsal, Marsal; Febrian, Muh. Fadli; Erwina, Erwina; Munawir, Munawir; Nurjannah, Nurjannah (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to analyze the influence of Work-Life Balance, Social Capital, and Knowledge Management on improving the performance of women's MSMEs in Palopo City. MSMEs play a strategic role in the Indonesian economy by absorbing most of the workforce and contributing significantly to the national GDP. In Palopo City, the majority of MSMEs are managed by women who face dual challenges as entrepreneurs and homemakers. The research employs a quantitative method, with women MSME respondents selected through an incidental sampling technique, yielding a sample size of 200. Data analysis uses Structural Equation Modeling-Partial Least Squares (SEM-PLS). The research results show that all variables have positive and significant effects on MSME performance. Knowledge Management provides the most substantial contribution, followed by Work-Life Balance and Social Capital. These findings confirm that the ability to manage knowledge becomes the main competitive advantage in the digital era, while work-life balance and social capital remain vital in business success. Respondents are predominantly in productive age groups, married, have secondary or higher education levels, and fall into the micro-enterprise category. This research provides theoretical contributions to the development of models of women's MSME performance and practical recommendations for women's economic empowerment policies that consider holistic aspects, including knowledge management, work-life balance, and social capital development. Practical implications indicate the need for a comprehensive approach to MSME empowerment programs that not only focus on technical business aspects but also consider knowledge management, work-life balance, and social network development to achieve optimal performance.